Estudio de cargabilidad de transformadores en el alimentador 52c8l4 subestación el calvario “Latacunga Sur” de la Empresa Eléctrica provincial Cotopaxi S.A en base al tipo de usuario y consumo de energía - Carrillo Pérez, Cristian Iván (2015)
The present research was developed in a study related to the use of the charge in transformers, which determines the proper operation of the electricity distribution without inconvenient due to energy losses, taking into consideration that during the operation of equipment has to deprive or prejudice of electric power to the lower number users whit this Electric Provincial Cotopaxi S.A. Company, has begun technical studies of charge, for the purpose of study, 52C8L4 feeder was taken in order to take advantage of the charge of the transformers installed in the feeder, intends to improve the distribution of power with actual consumption data from users connected to the distribution network and measurements to the transformers, It will allow relocating transformers that overloads and loss of energy in the system, and to propose a solution in the feeder, all results will be determined using the digital modeling in the Cymdist Software....